Mewujudkan Kesadaran Baru dan Perubahan Positif di Komunitas Mahasiswa Melalui Pelatihan Menulis Makalah Ilmiah - Khasanah, Umul; Rahmawati, Sintia; Fitriani, Fitriani; Nuzulla, Allieda Firdausi; Laksana, M. Ary Setiya (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to improve the ability to write scientific papers in damping communities that face limited accessibility to formal education and academic resources. The approach is carried out through intensive training programs, mentoring, and ongoing mentoring. This program is supported by the theories of community empowerment, social learning, and social transformation. The results of these activities include the emergence of new institutions, changes in behavior, and increased local leadership in the community. In addition, members of the attenuation community also gain a new awareness of their potential in the academic world, allowing them to more actively contribute to discussing and solving the various problems they face. Thus, this program succeeded in having a significant impact on increasing the community's accessibility to the academic and scientific world, bringing positive changes that could be felt by their community.